2014
DOI: 10.1186/2045-3701-4-24
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells cooperate with fractional carbon dioxide laser in antagonizing photoaging: a potential role of Wnt and β-catenin signaling

Abstract: BackgroundIt is well established that adipose-derived stem cells (ADSCs) produce and secrete cytokines/growth factors that antagonize UV-induced photoaging of skin. However, the exact molecular basis underlying the anti-photoaging effects exerted by ADSCs is not well understood, and whether ADSCs cooperate with fractional carbon dioxide (CO2) laser to facilitate photoaging skin healing process has not been explored. Here, we investigated the impacts of ADSCs on photoaging in a photoaging animal model, its asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…We suggested that ASCs significantly accelerated the re-epithelialization. And another studies showed that ASCs promote the growth of dermal fibroblasts by not only through intercellular cell-to-cell contact, but also by paracrine activation of marginal cells [13,14]. Recently, ASCs were found to accelerate wound healing in human cutaneous wounds [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggested that ASCs significantly accelerated the re-epithelialization. And another studies showed that ASCs promote the growth of dermal fibroblasts by not only through intercellular cell-to-cell contact, but also by paracrine activation of marginal cells [13,14]. Recently, ASCs were found to accelerate wound healing in human cutaneous wounds [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies suggest that transplanted ASCs accelerate wound healing by expanding the fibroblasts phenotype and increasing the supply of macrophages to the wound, enhancing granulation tissue formation [10][11][12]. Further studies showed that ASCs promote the growth of dermal fibroblasts through not only intercellular cell-to-cell contact, but also by paracrine activation of marginal cells [13][14][15][16]. The ASCs with conditioned media (CM) can stimulate the synthesis of dermal collagen and promote the migration of fibroblasts into the dermis, which are reported to help wrinkle improvement, facial defect filling, and wound healing compared with only ASCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…These results using EpSCs agree with previous reports that Nanog can promote proliferation and inhibit differentiation of stem cells. On the other hand, accumulating evidence indicates that the Wnt/β-catenin signaling pathway plays a critical role in the lineage decision/commitment process [ 10 , 23 , 27 , 28 ]. In contrast, there are also some reports that the Wnt/β-catenin signaling pathway plays a pivotal role in the maintenance of pluripotency as well as in the process of somatic cell reprogramming [ 9 , 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The co-culture cells were divided into 3 groups: HSF2 + ADSCs (NC), HSF2 + ADSCs + empty plasmid control group (EPC) and HSF2 + ADSCs + klotho OE group (OE). The co-culture system was achieved according to a previous report ( 22 ). Briefly, ADSCs and HSF2 were mixed and incubated with complete DMEM containing 10% FBS with 100 U/ml penicillin/streptomycin in a humidified atmosphere at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%